A treatise on physical chemistry : A Co-operative effort by a Group of Physical Chemists. - Taylor, Hugh S. (D. van Nostrand, 1942)
The atomic concept of matter - Quantum theory of atomic spectra and atomic structure - The first and second laws of thermodinamics - The third law of thermodinamics and statistical mechanics - Appendix.